A Retrospective Analysis of Treatment of Covid-19 with Favipiravir - Aigul Utegenova; Sholpan Kulzhanova; Maiya Konkayeva; Zauresh Smagulova; Nazira Beisenbieva; Gulnara Tuleshova (Journal of Biomedical & Clinical Research, 2022)
One of the potential therapeutic agents for treating COVID-19 is favipiravir (FPV). This retrospective study compared the treatment of COVID-19 with (FVP group) or without (control group) favipiravir. Demographic characteristics and initial clinical indicators in the two groups were comparable. The level of oxygen saturation, respiratory rate, and prevalence of chest pain in the FVP group returned to normal significantly earlier (on the seventh day) compared to the control group (p